The positive effects of increased foot patrols on the incidence of liquor infractions and assaults in the Granville Street Entertainment Area of Vancouver British Columbia Canada. (October 2017) - Fitterer, Jessica L.; Nelson, Trisalyn A.; Stockwell, Timothy
Abstract: Entertainment districts have high crime rates. Offences peak on the weekend during the operating hours of on-premises drinking establishments. To determine if proactive policing from May 1st to August 31st reduced the spatial density (kernel) or annual frequency of liquor infractions and assaults in Vancouver British Columbia Granville St. Entertainment Area (GEA) we analyzed the spatial and temporal pattern of crime pre (2006) and post (2010, 2013) the policing intervention. Crime occurred most frequently between 1:00am and 3:00am. The frequency of weekend liquor infractions significantly (α < 0.05) decreased during the proactive policing period. The magnitude of the reduction was greater for liquor infractions than assaults. Liquor infractions decreased from 121 events in 2006, to 53 events in 2010, to 91 events in 2013. Assaults decreased from 36 events in 2006, to 34 events in 2010, to 28 events in 2013. Future patrolling should focus on north-east end of Granville St. during early morning hours (1:00am-3:00am), and consider additional patrols, to increase crime reductions. In light of the recent trend to liberalize alcohol access across British Columbia we demonstrated that targeted policing strategies can reduce alcohol-attributable crime. We also provide fine temporal and spatial scale information on the patterns of crime creating evidence-based information to support policing strategies. Highlights: Drinking venues in entertainment districts increase the probability of crime. We analyzed if proactive-policing could significantly reduce crime. Proactive policing significantly reduced liquor crimes. Future patrolling should target problem venues at the north-east end of the entertainment area.